A research study of the views of scholars in determining the interpretation of Jawame ’al-Kalim - Sarfraz Ali; Dr. Anwarullah (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Eloquence is a miracle of the Holy Prophet (peace and blessings of Allah be upon him). His speech encompasses all aspects of the beautiful talk. His speech is a manifestation of the Divine Word as Almighty Allah says in Holy Quran “He does not speak from his own desire.”There are two aspects of the talk of the Prophet (peace and blessings of Allah be upon him). One is recited and the other is non-recited. Holy Prophet (peace and blessings of Allah be upon him) says I have been given “Jawame-Alkalim”. His quality of “Jawame-Alkalim” is related to recited revelation or non-recited is also included in this issue. Scholars have different views. This research article analyzes the views of scholars. This research paper looks into the outwards qualities of the Holy prophet’s speech and investigates the spiritual virtues of the Holy Prophet’s talk. This research article will be a prelude for Seerah researchers while researching and investigating the qualities of the Speech of the Prophet (peace and blessings of Allah be upon him).